2000
DOI: 10.1300/j077v18n03_03
|View full text |Cite
|
Sign up to set email alerts
|

Partners of Cancer Patients

Abstract: Although the adjustment of cancer patients' partners has been studied more extensively in recent years than previously, three areas of research have not been integrated into the literature: (1) the impact of cancer on the partner across different stages of the illness trajectory, (2) gender differences in partner's reactions and adjustment, and (3) psychosocial interventions for partners. In Part I of their review, the authors discussed the partners' experiences, how the illness affected partners, and how part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…In line with the fact that partners are (often) unaware of their own health complaints and therefore do not ask for help [9,14,40], participants in this study rated the topic “taking care of oneself” as less important than the other topics. Based on these outcomes, we think it is essential that an intervention targeting this group should be framed as informal and easily accessible support, from a positive perspective.…”
Section: Discussionmentioning
confidence: 99%
“…In line with the fact that partners are (often) unaware of their own health complaints and therefore do not ask for help [9,14,40], participants in this study rated the topic “taking care of oneself” as less important than the other topics. Based on these outcomes, we think it is essential that an intervention targeting this group should be framed as informal and easily accessible support, from a positive perspective.…”
Section: Discussionmentioning
confidence: 99%
“…It is generally accepted that cancer is a family affair. Not only the patient, but everybody who loves him/her also faces the consequences of the disease and treatment, which may include disruptions to their daily lives, anxiety, fears about cancer recurrence, and fears of loss and death ( 2 - 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…Dyadic research has found that coping with cancer treatment can challenge a couple's established communication patterns, roles, and responsibilities , leading to significant adjustment issues, communication difficulties, decreased intimacy and greater interpersonal conflict over time . In a study of 189 patients with localized prostate cancer and their female partners, partner's mental health was most affected by the mental health and by the physical complaint of sexual bother .…”
mentioning
confidence: 99%